Comparisons of Treatment for HER2-Positive Breast Cancer between Chinese and International Practice: A Nationwide Multicenter Epidemiological Study from China. (15th September 2021) - Han, Yi-Qun; Yi, Zong-Bi; Yu, Pei; Wang, Wen-Na; Ouyang, Qu-Chang; Yan, Min; Wang, Xiao-Jia; Hu, Xi-Chun; Jiang, Ze-Fei; Huang, Tao; Tong, Zhong-Sheng; Wang, Shu-Sen; et al.
Abstract : Objective . To better understand the status of medical treatment for human epidermal growth factor receptor 2 (HER2)-positive breast cancer and the differences between the Chinese and the international clinical practice. Methods . This was a retrospective, nationwide, multicenter, epidemiological study of advanced breast cancer patients from China. Between January 01, 2012, and December 31, 2014, a total of 3649 patients, covering 7 geographic regions and 21 institutions, participated in this series of studies. HER2-positive breast cancer was selected among the group and adopted into this study. In comparison, we summarized the demographics and clinical characteristics of HER2-positive breast cancer from the Surveillance, Epidemiology, and End Results (SEER) database. Results . A total of 918 patients diagnosed as HER2-positive breast cancer patients were included. The median age at diagnosis was 46 years (ranging, 23 to 78) with a single-peak incidence. The proportions of stages II–IV at diagnosis and distance metastasis in viscera were more than half of the participants. In comparison, the prevalence of estrogen or progesterone receptor-positive expression and luminalB subtype was relatively lower than that of the United States. The receipt of chemotherapy was fairly higher, while the usage of targeted therapy was seriously insufficient. Tumor size was in significantly positive associations with the duration of targeted therapy (Kendall's correlation coefficient = 0.3, P < 0.0001 ), while no prohibitive variables among clinical characteristics were detected. Conclusion . Our study suggested that HER2-positive breast cancer patients were characterized as a younger trend, a lower prevalence of hormonal receptor (HR)-positive expression, and less accessible to anti-HER2 targeted therapy with insufficient duration over the past few years in China. Concerted efforts should be exerted for promising survival benefits in the future. The trial registration number is https://clinicaltrials.gov/ct2/show/NCT03047889 .